Gender Differences Influence Gender Equality Awareness, Self-Esteem, and Subjective Well-Being Among School-Age Children in China - Li, Yifei; Zuo, Man; Peng, Yirong; Zhang, Jie; Chen, Yiping; Tao, Yingxiang; Ye, Biyun; Zhang, Jingping (Frontiers in Psychology, 2022)
The objective of this study was to investigate and analyze the status and influential factors of gender equality awareness, self-esteem, and subjective well-being in school-age boys and girls. The results can help schools and teachers provide more effective gender equality and mental health education. In the study, 284 valid questionnaires were collected from a total of 323 school-age boys and girls in the Hunan Province, China (effective response rate of 87.93%). The questionnaire covered gender equality awareness, self-esteem, and subjective well-being, with the influencing factors analyzed through multiple linear regression. There was a significant correlation among children’s gender equality awareness in all areas examined (family, occupation, and school), with both boys and girls having the lowest awareness of gender equality in occupational fields. The children’s self-esteem and subjective well-being were significantly correlated as well. Gender equality awareness, self-esteem, and subjective well-being among boys and girls reflected different influential factors. Androgynous traits (neither feminine nor masculine) were conducive to the development of gender equality awareness and self-esteem among the children. Therefore, schools and teachers need to provide gender equality and mental health education according to the specific psychological characteristics of each boy and girl.